×

# Phasor subtraction question

1. Junior Member
Join Date
Mar 2015
Posts
10
Reputation

## Phasor subtraction question

I had a question very similar to this.

If a phasor B = 6 – j2 is subtracted from phasor A = -4 + j3, what is the resulting phasor C?

Any idea how to solve for it?

Thanks,
John

2. Junior Member Pro Subscriber
Join Date
Sep 2019
Posts
1
Reputation
Originally Posted by jfoster
I had a question very similar to this.

If a phasor B = 6 – j2 is subtracted from phasor A = -4 + j3, what is the resulting phasor C?

Any idea how to solve for it?

Thanks,
John
John,

This is one of those questions that seems more complicated than it really is. This form of phasor is Z=R+jX where R is the real part of the phasor, and X is the imaginary part of the phasor. When adding/subtracting in this form, it is as easy as adding/subtracting each part of the phasor individually. Given phasor Z1 and phasor Z2, Z1-Z2=(R1-R2) + j(X1-X2) So, C = A - B = [(-4)-6] +j[3-(-2)] = -10 + j5. This only works for addition and subtraction. I hope this helps!

Dana

3. Junior Member
Join Date
Mar 2015
Posts
10
Reputation
Originally Posted by dash1911
John,

This is one of those questions that seems more complicated than it really is. This form of phasor is Z=R+jX where R is the real part of the phasor, and X is the imaginary part of the phasor. When adding/subtracting in this form, it is as easy as adding/subtracting each part of the phasor individually. Given phasor Z1 and phasor Z2, Z1-Z2=(R1-R2) + j(X1-X2) So, C = A - B = [(-4)-6] +j[3-(-2)] = -10 + j5. This only works for addition and subtraction. I hope this helps!

Dana
Thank you

Related Content